Devotion and dissent in Indian history - Vijaya Ramaswamy
Papers presented at the international conference on 'Devotion and Dissent in Indian History', held at New Delhi during 11-13 March 2010; hosted by Centre for Historical Studies, Jawaharlal Nehru University.